White Christmas [videorecording (DVD)] - Berlin, Irving, 1888-1989 (Paramount, 2019)
When two song-and-dance men join forces with a sister act and travel to Vermont in search of a white Christmas, they find that the inn is run by their old army general, who is now in financial trouble.